Penerapan Sistem Penjualan dengan modul Ecommerce pada Kiva Betta Fish Berbasis Odoo - Michel Gusti Rifadi; Lufty Abdillah (UNIVERSITAS KALBIS, 2022)
Currently, the development of technology, especially in Indonesia, has been very rapid, starting from the existing technology on mobile phones (smartphones), computers, to internet networks that can help facilitate all human needs. Especially web sites, there are now many companies that use the site as the identity of the company itself. Not only big companies, but there are also many small companies or UMKM that use the website as a means to promote and sell products. Kiva Betta Fish is a business that sells various types of betta fish and other fish needs. from various types of fish, ranging from fish food, fish food, and fish medicine. And Kiva Betta Fish requires a website- based application system in the form of ecommerce for promotion and ordering goods to make business processes easier.